Windows 8 - Sosinsky, Barrie A. (Visual quickstart guide., 2013)
A comprehensive guide to Windows 8, that explains what Windows 8 can and cannot do, how it works, how to manage it, what fun applications it has, how to keep it safe, and what hardware options the operating system supports.--